Engineering extracellular vesicles with macrophage membrane fusion for ameliorating imiquimod-induced psoriatic skin inflammation - Zeng Wang; Zhizhen Qin; Jiadie Wang; Xinqi Xu; Mengxin Zhang; Yuyue Liang; Yukun Huang; Zengyang Yu; Yu Gong; Luxian Zhou; Yiran Qiu; Minglu Ma; et al. (Taylor & Francis Group, 2023)
Introduction Herein, we developed an engineered extracellular vehicle (EV)-based method for ameliorating inflammatory responses in psoriasis. Methods EVs, derived from annexin A1 (ANXA1) overexpressing T cells, were co-extruded with M2 macrophage membrane to obtain engineered EVs. In vitro, the effect of engineered EVs on macrophage polarization was evaluated by real-time PCR. In imiquimod (IMQ)-induced psoriasis-like mouse model, the efficacy of engineered EVs in ameliorating psoriatic inflammation was evaluated by Psoriasis Area and Severity Index (PASI) score and immunohistochemistry staining after subcutaneous injection of EVs. Results The engineered EVs not only preserved the high stability of M2 macrophage membrane but also retained the macrophage reprogramming potential of ANXA1 overexpressed in T cells. In the psoriasis-like mouse model, subcutaneous injection of engineered EVs successfully reduced the PASI score and the levels of pro-inflammatory cytokines, including IL-1β, IL-6, and TNF-α. Along with high biosafety, the administration of EVs also rescued the histomorphological changes of spleen, liver, and kidney. Conclusions The engineered EVs exhibited the potential to alleviate inflammation of psoriasis, providing new insights and potential strategies for the immunotherapies of psoriasis.